2007
DOI: 10.1037/1931-3896.1.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study on the healing nature of mandalas.

Abstract: Mandalas were first used in therapy by Carl Jung, who found that the act of drawing mandalas had a calming effect on patients while at the same time facilitating psychic integration. There is a scarcity of controlled empirical studies of the healing impact of mandalas on mental health. Based on the efficacy of James Pennebaker's written disclosure paradigm in promoting mental well-being (Pennebaker, 1997a, 1997b), the purpose of our study was to examine the benefits for those suffering from post traumatic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 28 publications
(40 reference statements)
2
100
0
4
Order By: Relevance
“…Recent studies have discovered that mandala could be a promising tool for non-verbal emotional communication [32,[34][35][36][37]. For patients with post-traumatic stress disorder (PTSD), therapists can diagnose patients' emotional statuses through the mandalas drawn by them, while these patients are not willing or not able to discuss sensitive information regarding childhood abuse [36].…”
Section: Archetypal Pictures and Soundsmentioning
confidence: 99%
“…Recent studies have discovered that mandala could be a promising tool for non-verbal emotional communication [32,[34][35][36][37]. For patients with post-traumatic stress disorder (PTSD), therapists can diagnose patients' emotional statuses through the mandalas drawn by them, while these patients are not willing or not able to discuss sensitive information regarding childhood abuse [36].…”
Section: Archetypal Pictures and Soundsmentioning
confidence: 99%
“…In other words, the compositional complexity of the mandala aroused more cognitive interest, but this did not necessarily create more feelings of calm and happiness, which were induced by the flowers. This finding is interesting in light of the common use of manadalas to create calm and positive emotions in therapeutic interventions [38]. From this, then we see that flowers are better at inducing positive emotions.…”
Section: Resultsmentioning
confidence: 65%
“…In other words, we see that the shape and size-the visual characteristics of the flower, induces emotional reactions of aesthetic pleasure and calmness. This follows the literature that connects between aesthetic characteristics and induction of emotions [34,38]. However, there is not one specific shape that arouses more pleasure, because the 1 st choice was dispersed.…”
Section: Variations In Choice Of Flowermentioning
confidence: 76%
“…In a randomized controlled trial, Henderson et al (2007) studied two groups of adults with PTSD symptoms; the experimental group depicted trauma-related feelings and emotions within a circle, and the control group drew assigned daily objects such as a cup. At a 1-month follow-up session, the researchers found that participants in the experimental group experienced greater reduction in PTSD symptoms-but not in depression or anxiety symptoms-than control group participants.…”
Section: Results Of Prior Studies Of Art Therapy For Ptsdmentioning
confidence: 99%
“…Art therapy may assist with integration of sensory memories and declarative memory and has been shown to reduce symptoms of PTSD in a number of populations (Harber, 2011;Henderson, Rosen & Mascaro, 2007;Lyshak-Stelzer, Singer, St. John, & Chemtob, 2007;Pifalo, 2007Pifalo, , 2009Tripp, 2007); however, there are no known randomized controlled trials on the effects of art therapy on combat-related PTSD. In a 2013 Delphi study (Kaiser & Deaver, 2013), a panel of expert art therapy researchers identified randomized controlled trials as the highest priority for the art therapy field, and trauma as the most important psychological construct to address through research.…”
Section: Introductionmentioning
confidence: 99%